THE WAR OF THE WORLDS - Wells, H.G., (Herbert George), 1866-1946.; Miller, Harry; Cameron, Lou (Newbury, Berkshire : CCS Books, 2019)
Wells's science fiction tale of the Martian invasion, told through the eyes of an ordinary man, in colorful comic strip form, providing a simplified introduction for younger readers. The book also includes theme discussions and study questions.
Primary.
Keywords: Wells, H. G. -- 1866-1946. -- Adaptations; Imaginary wars and battles -- Comic books, strips, etc; Space warfare -- Comic books, strips, etc; Mars (Planet) -- Comic books, strips, etc; Graphic novels; Comics adaptations